The Cambridge history of capitalism / edited by Larry Neal and Jeffrey G. Williamson. - Neal, Larry; Williamson, Jeffrey G., 1935- (Cambridge : Cambridge University Press, 2014)
"Modern economic growth, defined as a sustained rise in per capita income (Kuznets 1966C001-025), has created higher levels of prosperity for many more people on earth than was ever thought possible before it began. Moreover, it began not so very long ago, perhaps as late as the middle of the nineteenth century and certainly not before the end of the seventeenth century"--
volume 1. The rise of capitalism: from ancient origins to 1848 -- volume 2. The spread of capitalism: from 1848 to the present --
Includes bibliographical references and index.
Keywords: Capitalism -- History; Economic history; BUSINESS & ECONOMICS / Economic History